(3GdGZJHGW HJQGLe CYdGe GdQHGWs - (3CHh YHO Gddg eMeO Hf eUWaj HhLfOGQ GdQHGWj,J (B1345 (3g` s
(3ChdgG (B:s
(3bGd eDdag SGeMg Gddg (B: (3dGHO ai cd eTQhY ef aGJMI jHJOC HgG bHd GdTQhY , haGJMI eTQhYi gPG CMeO ef LYd SjQI GdZGHQjf s
(3BNQgG (B:s
(3dPG CJj ef haGb JGQjNg GdEZJHGW s
(3hQOJ ai agQSJ GdNRGfI GdYGeI HGdQHGW(B226/2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B102s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B40 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B226 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B1287) s
Keywords: (3GdJGQjNs